A high-strength and toughness dual-phase low-density steel and its preparation method and application

By optimizing chemical composition and heat treatment process, avoiding the precipitation of κ carbides, the problems of poor work hardening capabilities and high yield and strength ratio of low-density steel are solved, and the high strength and toughness of the material are achieved, and the production cost is reduced.

CN116288021BActive Publication Date: 2025-03-04WUHAN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310100007.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-06
Publication Date
2025-03-04
Estimated Expiration
2043-02-06

AI Technical Summary

Technical Problem

Existing low-density steels are prone to form κ carbides after heat treatment, resulting in a reduced work hardening capacity and an excessively high yield-strength ratio, which is not conducive to complex molding.

Method used

By optimizing chemical composition and heat treatment processes, reducing carbon content, controlling the mass ratio of Mn and Al, and avoiding the precipitation of κ carbides, multi-pass hot rolling and cold rolling processes are used, combining stress annealing and specific annealing treatment to adjust the austenite and ferrite structure of the material.

Benefits of technology

It achieves good work hardening properties of the material, does not reduce tensile strength and plasticity, and the yield-strength ratio is below 0.5, which can meet the complex molding needs of automobile boards and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004072883800000121
    Figure BDA0004072883800000121
  • Figure HDA0004072883820000011
    Figure HDA0004072883820000011
  • Figure HDA0004072883820000012
    Figure HDA0004072883820000012
Patent Text Reader

Abstract

The present invention relates to the technical field of low-density steel preparation, and specifically to a high-strength and toughness dual-phase low-density steel and a preparation method thereof. The high-strength and toughness dual-phase low-density steel provided by the present invention reduces the carbon content through component design, and at the same time, by controlling the mass ratio between Mn and Al and coordinating with a specific treatment process, the precipitation of κ carbide in the material matrix structure is avoided, thereby ensuring the good work hardening performance of the material, and not reducing the tensile strength and plasticity of the material. The prepared material has a yield strength of not less than 430MPa, a tensile strength of not less than 1050MPa, an elongation after fracture of not less than 34%, a yield strength ratio of 0.4 to 0.5, and a density of 6.84g / cm 3 About 10000 square meters, which can meet the complex forming requirements of automobile plates. Compared with austenitic low-density steel, it reduces the alloy content, reduces the difficulty of material smelting and production, and reduces the cost. Compared with traditional dual-phase low-density steel, it avoids the precipitation of kappa carbide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of low-density steel preparation, and in particular to a high-strength and toughness dual-phase low-density steel and a preparation method and application thereof. Background Art

[0002] In order to improve energy utilization and achieve energy conservation and emission reduction, lightweighting has become a new trend in the development of the modern automobile industry, and lightweighting of the car body is an important way to achieve lightweighting of automobiles. High-strength steel can be used instead of traditional steel for car body components, and lightweighting can be achieved by reducing the thickness of steel plates. At present, the third-generation high-strength steel under development is represented by low-density steel, medium manganese steel, and QP steel. The strength-plasticity product can reach 20-40GPa%, and the alloy content is lower than that of the second-generation high-strength steel, which relatively reduces the production cost. Among them, Fe-Mn-Al-C low-density steel has ultra-high strength and high plasticity, while the density can be reduced by 6-18% compared with traditional steel. It is a research hotspot in the third-generation high-strength automotive steel.

[0003] Fe-Mn-Al-C low-density steel achieves a reduction in material density by adding a higher Al element, and a higher Mn and C elements are added to improve the stability of austenite in the steel. According to the different matrix structures, low-density steel can be divided into two categories: austenitic low-density steel and ferrite-austenite dual-phase low-density steel: the matrix structure of austenitic low-density steel is a single austenite phase, and a large amount of manganese elements need to be added to maintain the stability of austenite, which is costly; ferrite-austenite dual-phase low-density steel reduces the manganese content on the basis of the former, and its matrix structure is austenite + body, but due to the addition of higher alloying elements, the ferrite strength in the dual-phase low-density steel is higher, and the increase in ferrite content will increase the yield strength of the material and reduce the plasticity of the material.

[0004] Due to the high content of alloying elements, traditional low-density steel is prone to precipitation of (Fe, Mn) 3AlCx type carbides (κ carbides) after heat treatment, which has a significant impact on material properties. Austenitic low-density steels are often heat-treated to control the number and size of κ carbides, and use precipitation strengthening to obtain high tensile strength and high elongation, but the precipitation of carbides hinders dislocation slip, reduces the material's work hardening ability, and the yield strength ratio is close to 1, which is not conducive to complex forming. For example, the patent with publication number CN115323278A discloses a yield grade 700MPa low-density steel and its heat treatment method, whose components by weight percentage are: C: 0.85-1.15%, Mn: 25-35, Al: 9.0-11.0%, Nb: 0-0.2%, Mo: 0-0.2%, V: 0-0.2%, Ti: 0-0.2% and Zr: 0-0.2%, wherein the total amount of Nb, Mo, V, Ti and Zr is not less than 0.05%, and the balance is Fe and unavoidable impurities. After smelting, it is cast into ingots or billets, heated at 1100-1200℃, and hot rolled or forged at 800-1150℃ to form plates and bars with a thickness or diameter of 20mm; the plates or bars are kept at 950-1150℃ for 0.1-10 hours, then water-cooled or oil-cooled for solution treatment; the material after solution treatment is kept at 400℃ for 20-80 hours, and subjected to low-temperature long-term aging treatment. The yield strength of austenitic low-density steel produced by this technology reaches 703-790Mpa, the tensile strength is 870-930MPa, the yield strength ratio is 0.78-0.82, the elongation is 51-62%, and the work hardening ability is poor.

[0005] κ carbide is easy to precipitate at the grain boundary in dual-phase low-density steel. When the precipitate size is small and the content is low, it can play a strengthening role, improve the yield strength of the material, and reduce the work hardening ability. When the precipitate size is coarse, the plasticity of the material will be significantly reduced. For example, the invention with publication number CN108018494B discloses an annealing process for improving the strength and plasticity of low-density steel and a production method for low-density steel, and its composition mass percentage is Mn: 19.40% to 20%, Al: 9.82 to 10%, C: 0.98 to 1%, P≤0.003%, S≤0.003%, and the rest are unavoidable impurities. After smelting, it is cast into a casting billet, heated to 1150-1250° C. and kept warm, and then subjected to at least two hot rollings; the hot-rolled plate is kept warm at 1000-1100° C. and then subjected to quenching treatment, and at least two cold rollings are carried out, and the cumulative deformation of the cold rolling is 67%; the cold-rolled plate is subjected to the following annealing treatment: the cold-rolled plate is heated to 1000-1100° C., kept warm for 3-4 hours, and subjected to a primary austenitizing treatment; then the plate temperature is cooled to 650-750° C., kept warm for 2-3 hours, and subjected to a carbide treatment; the plate temperature is raised to 850-950° C., kept warm for 1-3 hours, and subjected to a secondary austenitizing treatment; the plate is water-cooled to room temperature. The low-density steel produced by this technology has a dual-phase structure, and its performance is significantly affected by changes in annealing temperature: when the κ carbide content is controlled at 10-20% after treatment, the material's yield strength reaches 920MPa, tensile strength is 1080MPa, yield strength ratio is 0.85, and elongation is 48%; when the κ carbide content is greater than 20%, the material's elongation is only 10%; when the κ carbide content is less than 10%, the strengthening effect is not obvious, the yield strength is 575MPa, and the tensile strength is 805MPa.

[0006] It can be seen that the precipitation of κ carbide in austenitic low-density steel will significantly reduce the material's work hardening ability, making the material's yield strength ratio too high, which is not conducive to the material's complex forming. When the κ carbide content in dual-phase low-density steel is too low, the material strengthening effect is not obvious, and when it is high, it will significantly reduce the material's plasticity. In order to control the size and amount of carbide precipitation, a complex heat treatment process is required, which is costly. In addition, this type of steel has poor work hardening ability and a high yield strength ratio, which is also not conducive to the material's complex forming. Summary of the invention

[0007] Based on this, the purpose of the present invention is to provide a high-strength and toughness dual-phase low-density steel and its heat treatment process. Through component design and reasonable treatment process, the precipitation of κ carbide is avoided. While ensuring the good work hardening performance of the material, the tensile strength and plasticity of the material are not reduced. The prepared low-density steel has a yield strength ratio of less than 0.5, which can meet the complex forming requirements of automotive panels.

[0008] The present invention achieves the above technical objectives through the following technical solutions:

[0009] The present invention provides a high-strength and toughness dual-phase low-density steel, wherein the chemical composition mass percentage of the high-strength and toughness dual-phase low-density steel is: C: 0.58-0.62%, Mn: 18-22%, Al: 7-9%, Nb: 0-0.02%, and the rest is Fe and inevitable impurities, wherein the mass ratio of Mn to Al is 2.4-2.6; the preparation method is as follows:

[0010] Smelting and casting: conventional smelting and continuous casting, the thickness of the casting is controlled at 60-150mm;

[0011] Primary dephosphorization: high-pressure water dephosphorization is performed before the ingot enters the furnace;

[0012] Homogenization: Keep the ingot at 1100-1200℃ for 1.5-3 hours for homogenization;

[0013] Secondary dephosphorization: The ingot after homogenization treatment is subjected to secondary high-pressure water dephosphorization;

[0014] Hot rolling: the ingot after secondary dephosphorization is subjected to multiple hot rolling, wherein the starting rolling temperature is controlled at 1050-1100°C, the final rolling temperature is controlled at 850-910°C, and the rolling is performed to a thickness of 2.5-4.5 mm;

[0015] Cooling and coiling: The hot rolled material is cooled to 625-675°C and coiled at this temperature;

[0016] Stress relief annealing: Keep the coiled material at 450-550℃ for 8-15min for stress relief annealing;

[0017] Cold rolling: After stress relief annealing, multiple cold rolling is carried out, with a cumulative deformation of 45-55%, and the thickness is rolled to 1.15-2.25mm;

[0018] Annealing treatment: when no Nb is contained, the cold-rolled sheet is kept at 650-950°C for 25-35 minutes, and water quenched to cool to room temperature to obtain the product; when Nb is contained, the cold-rolled sheet is kept at 750-950°C for 25-35 minutes, and water quenched to cool to room temperature to obtain the product.

[0019] As a preferred embodiment, the superheat of the molten steel is controlled at 15-30°C during pouring.

[0020] As a preferred embodiment, the pressure of the dephosphorization water is 300-400 bar during the primary dephosphorization, and the pressure of the dephosphorization water is 300-410 bar during the secondary dephosphorization.

[0021] As a preferred embodiment, the ingot after secondary dephosphorization is subjected to 5 hot rolling passes, wherein the reduction ratios of the 1st to 4th passes are 40-55%, and the reduction ratio of the 5th pass is 25-35%.

[0022] As a preferred embodiment, the hot-rolled material is cooled by water curtain cooling or laminar cooling.

[0023] As a preferred implementation, 2 to 3 cold rolling passes are performed after stress relief annealing.

[0024] As a preferred embodiment, during the annealing treatment, the cold-rolled sheet is kept warm by vacuum heating.

[0025] As a preferred embodiment, the mass percentage of Mn is 19.5-20.5%, and the mass percentage of Al is 7.8-8.2%.

[0026] As a preferred embodiment, the homogenization temperature is 1130-1160°C, the final rolling temperature is 875-885°C, and the coiling temperature is 640-660°C.

[0027] The present invention also aims to protect the application of the high-strength and toughness dual-phase low-density steel in complex forming of automobile plates.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention reduces the carbon content by component design, controls the mass ratio between Mn and Al, and cooperates with a specific treatment process to avoid the precipitation of kappa carbide in the material matrix structure, ensures good work hardening performance of the material, and does not reduce the tensile strength and plasticity of the material. The prepared material has a yield strength of not less than 430MPa, a tensile strength of not less than 1050MPa, an elongation after fracture of not less than 34%, a yield strength ratio of less than 0.5, and a density of 6.84g / cm 3 About 1000 square meters, which can meet the complex forming requirements of automobile plates. Compared with austenitic low-density steel, it reduces the alloy content, reduces the difficulty of material smelting and production, and reduces the cost. Compared with traditional dual-phase low-density steel, it avoids the precipitation of kappa carbides, improves the material processing hardening ability, does not require complex heat treatment processes, and reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The XRD scanning patterns of the high-strength and toughness dual-phase low-density steels prepared in the examples and comparative examples after annealing;

[0031] Figure 2 : is the true stress-strain curve of the high-strength and toughness dual-phase low-density steel prepared in the examples and comparative examples, wherein a is the strain curve of the low-density steel prepared in examples 1 to 3, and b is the strain curve of the low-density steel prepared in examples 4 to 5 and comparative example 1. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.

[0033] The following embodiments are only used to illustrate the present invention, but are not used to limit the scope of the present invention. Based on the specific embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention.

[0034] In the examples of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the examples of the present invention, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.

[0035] The present invention provides a high-strength and toughness dual-phase low-density steel, the composition of which is as follows: C0.58-0.62%, Mn 18-22%, Al 7-9%, Nb 0-0.02%, and the rest is Fe and inevitable impurities, wherein the mass ratio of Mn to Al is 2.4-2.6. The role and proportion of each element are as follows:

[0036] Al: ferrite forming element. The increase of Al content will increase the proportion of ferrite, increase the yield strength of the material and reduce the plasticity. At the same time, Al is a lightweight element and can reduce the density of the material. To ensure that the material has high yield strength and low density, the Al content shall not be less than 7%. To ensure that the material has high toughness, the Al content shall not be higher than 9%;

[0037] Mn: Austenite stabilizing element. The increase of Mn content can expand the austenite phase area and improve the stability of austenite. In order to improve the stability of austenite and ensure that austenite is the matrix structure, the Mn content must be greater than 18%. However, when the Mn content is too high, β-Mn brittle phase is easily formed in austenite, which greatly reduces the density of the material. Therefore, the Mn content shall not be higher than 22%;

[0038] C: An important solid solution strengthening element and austenite stabilizing element. To ensure the yield strength of the material and improve the stability of austenite, the C content must not be less than 0.58%. An increase in the C content will promote the precipitation of κ carbides. To avoid carbide precipitation, the C content must not be higher than 0.62%.

[0039] Nb: A trace alloying element that can further improve the strength and plasticity of the material through grain refinement and precipitation strengthening. The strengthening effect of Nb on the material has a peak value. Too high Nb content does not significantly improve the material performance and increases the material production cost. Therefore, the Nb content needs to be controlled at 0-0.02%;

[0040] The ratio of ferrite to austenite is affected by the ratio of Mn to Al elements. Therefore, in order to meet the material performance requirements, the mass ratio of Mn to Al needs to be controlled at 2.4 to 2.6.

[0041] The preparation method of the high-strength and toughness dual-phase low-density steel is as follows:

[0042] Smelting and casting: conventional smelting (such as induction melting, electric furnace or converter smelting) and continuous casting, controlling the thickness of the casting to 60-150mm;

[0043] Primary dephosphorization: high-pressure water dephosphorization is performed before the ingot enters the furnace;

[0044] Homogenization: Keep the ingot at 1100-1200℃ for 1.5-3 hours for homogenization;

[0045] Secondary dephosphorization: The ingot after homogenization treatment is subjected to secondary high-pressure water dephosphorization;

[0046] Hot rolling: the ingot after secondary dephosphorization is subjected to multiple hot rolling, wherein the starting rolling temperature is controlled at 1050-1100°C, the final rolling temperature is controlled at 850-910°C, and the rolling is performed to a thickness of 2.5-4.5 mm;

[0047] Cooling and coiling: The hot rolled material is cooled to 625-675°C and coiled at this temperature;

[0048] Stress relief annealing: Keep the coiled material at 450-550℃ for 8-15min for stress relief annealing;

[0049] Cold rolling: After stress relief annealing, multiple cold rolling is carried out, with a cumulative deformation of 45-55%, and the thickness is rolled to 1.15-2.25mm;

[0050] Annealing treatment: when no Nb is contained, the cold-rolled sheet is kept at 650-950°C for 25-35 minutes, and water quenched to cool to room temperature to obtain the product; when Nb is contained, the cold-rolled sheet is kept at 750-950°C for 25-35 minutes, and water quenched to cool to room temperature to obtain the product.

[0051] Among them, the thickness of the ingot is controlled at 60-150mm, and the essential fine grain of the finished material structure of 1.15-2.25mm is achieved through appropriate slab thickness and large reduction in subsequent hot rolling and cold rolling processes, thereby improving the comprehensive mechanical properties of the material; the ingot is kept at 1100-1200℃ for 1.5-3 hours to improve the crystal structure of the ingot, eliminate casting stress, and reduce element segregation; the final rolling temperature is controlled at 850-910℃ because this temperature range can maximize the proportion of austenite structure and is used to regulate the ferrite-austenite ratio in steel. , in order to reduce the strength of steel and improve toughness; the coiling temperature is controlled at 625-675℃, because this temperature range can avoid the precipitation of κ carbide, improve the toughness of the material, and facilitate subsequent processing; during annealing, the heating temperature is controlled within a specific range and kept warm for 30 minutes to avoid the precipitation of κ carbide, while making the volume ratio of austenite structure inside the steel plate reach 85-90%, and retain a certain amount of ferrite. The austenite matrix can make the material obtain good tensile strength and elongation, and ferrite can improve the yield strength of the material. Adjusting the annealing temperature can adjust the yield strength ratio of the material.

[0052] In the whole production process, dephosphorization is carried out twice. By controlling the dephosphorization pass and the appropriate dephosphorization water pressure, the iron oxide scale on the surface of the strip is removed as much as possible to ensure its good surface quality.

[0053] Water quenching is selected after heat preservation because the high gold content improves the stability of austenite. Austenite can remain stable at high cooling rate without phase transformation. Water quenching to room temperature can maximize the volume ratio of austenite structure and avoid the precipitation of κ carbide during the cooling process, which reduces the toughness of the material.

[0054] Example 1

[0055] This embodiment provides a high-strength and toughness dual-phase low-density steel, the composition of which is as follows: C: 0.61%, Mn: 20.37%, Al: 8.12%, the rest is Fe and unavoidable impurities, and the mass ratio of Mn to Al is 2.5; the preparation method is as follows:

[0056] Smelting and casting: conventional smelting and continuous casting, the superheat of molten steel is controlled at 15-30℃ during casting, and the thickness of the casting is controlled at 62mm;

[0057] Phosphorus removal: high-pressure water is used to remove phosphorus before the ingot enters the furnace, and the pressure of the dephosphorus removal water is controlled at 345 bar;

[0058] Homogenization: Keep the ingot at 1150℃ for 2 hours for homogenization;

[0059] Phosphorus removal: secondary high-pressure water dephosphorization is carried out before rolling, and the dephosphorization water pressure is controlled at 370 bar;

[0060] Hot rolling: the homogenized ingot is hot rolled for 5 passes, the reduction ratios of the 1st to 4th passes are all 50%, the reduction ratio of the last pass is 35%, the starting rolling temperature is 1050°C, the final rolling temperature is 900°C, and the thickness of the hot rolled plate is about 2.4mm;

[0061] Cooling: Cool to the coiling temperature of 650℃ by laminar cooling and coil at this temperature;

[0062] Stress relief annealing: The coiled material is kept at 500℃ for 10 minutes for stress relief annealing;

[0063] Cold rolling: The plate after stress relief annealing is cold rolled for 3 times, with a cumulative deformation of 50%, and the thickness of the obtained cold rolled plate is about 1.2mm;

[0064] Annealing treatment: keep the cold-rolled sheet at 650℃ for 30min, and then cool it to room temperature by water quenching.

[0065] Example 2

[0066] This embodiment provides a high-strength and toughness dual-phase low-density steel, the composition of which is as follows: C: 0.61%, Mn: 20.37%, Al: 8.12%, the rest is Fe and unavoidable impurities, and the mass ratio of Mn to Al is 2.5; the preparation method is as follows:

[0067] Smelting and casting: conventional smelting and continuous casting, the superheat of molten steel is controlled at 15-30℃ during casting, and the thickness of the casting is controlled at 62mm;

[0068] Phosphorus removal: high-pressure water is used to remove phosphorus before the ingot enters the furnace, and the pressure of the dephosphorus removal water is controlled at 345 bar;

[0069] Homogenization: Keep the ingot at 1150℃ for 2 hours for homogenization;

[0070] Phosphorus removal: secondary high-pressure water dephosphorization is carried out before rolling, and the dephosphorization water pressure is controlled at 370 bar;

[0071] Hot rolling: the homogenized ingot is hot rolled for 5 passes, the reduction ratios of the 1st to 4th passes are all 50%, the reduction ratio of the last pass is 35%, the starting rolling temperature is 1050°C, the final rolling temperature is 900°C, and the thickness of the hot rolled plate is about 2.4mm;

[0072] Cooling: Cool to the coiling temperature of 650℃ by laminar cooling and coil at this temperature;

[0073] Stress relief annealing: The coiled material is kept at 500℃ for 10 minutes for stress relief annealing;

[0074] Cold rolling: The plate after stress relief annealing is cold rolled for 3 times, with a cumulative deformation of 50%, and the thickness of the obtained cold rolled plate is about 1.2mm;

[0075] Annealing treatment: keep the cold-rolled sheet at 800℃ for 30min, and then cool it to room temperature by water quenching.

[0076] Example 3

[0077] This embodiment provides a high-strength and toughness dual-phase low-density steel, the composition of which is as follows: C: 0.61%, Mn: 20.37%, Al: 8.12%, the rest is Fe and unavoidable impurities, and the mass ratio of Mn to Al is 2.5; the preparation method is as follows:

[0078] Smelting and casting: conventional smelting and continuous casting, the superheat of molten steel is controlled at 15-30℃ during casting, and the thickness of the casting is controlled at 62mm;

[0079] Phosphorus removal: high-pressure water is used to remove phosphorus before the ingot enters the furnace, and the pressure of the dephosphorus removal water is controlled at 345 bar;

[0080] Homogenization: Keep the ingot at 1150℃ for 2 hours for homogenization;

[0081] Phosphorus removal: secondary high-pressure water dephosphorization is carried out before rolling, and the dephosphorization water pressure is controlled at 370 bar;

[0082] Hot rolling: the homogenized ingot is hot rolled for 5 passes, the reduction ratios of the 1st to 4th passes are all 50%, the reduction ratio of the last pass is 35%, the starting rolling temperature is 1050°C, the final rolling temperature is 900°C, and the thickness of the hot rolled plate is about 2.4mm;

[0083] Cooling: Cool to the coiling temperature of 650℃ by laminar cooling and coil at this temperature;

[0084] Stress relief annealing: The coiled material is kept at 500℃ for 10 minutes for stress relief annealing;

[0085] Cold rolling: The plate after stress relief annealing is cold rolled for 3 times, with a cumulative deformation of 50%, and the thickness of the obtained cold rolled plate is about 1.2mm;

[0086] Annealing treatment: keep the cold-rolled sheet at 950°C for 30 minutes, and then cool it to room temperature by water quenching.

[0087] Example 4

[0088] This embodiment provides a high-strength and toughness dual-phase low-density steel, the composition of which is as follows: C: 0.61%, Mn: 20.47%, Al: 8.15%, Nb: 0.019%, the rest is Fe and unavoidable impurities, and the mass ratio of Mn to Al is 2.5; the preparation method is as follows:

[0089] Smelting and casting: conventional smelting and continuous casting, the superheat of molten steel is controlled at 15-30℃ during casting, and the thickness of the casting is controlled at 65mm;

[0090] Phosphorus removal: high-pressure water is used to remove phosphorus before the ingot enters the furnace, and the pressure of the dephosphorus removal water is controlled at 375 bar;

[0091] Homogenization: Keep the ingot at 1150℃ for 2 hours for homogenization;

[0092] Phosphorus removal: secondary high-pressure water dephosphorization is carried out before rolling, and the dephosphorization water pressure is controlled at 365 bar;

[0093] Hot rolling: the homogenized ingot is hot rolled for 5 passes, the reduction rate of the 1st to 4th passes is 50%, the reduction rate of the last pass is 35%, the starting rolling temperature is 1100°C, the final rolling temperature is 890°C, and the thickness of the obtained hot rolled plate is 2.6mm;

[0094] Cooling: Cool to the coiling temperature of 640℃ by laminar cooling and coil at this temperature;

[0095] Stress relief annealing: The coiled material is kept at 500℃ for 10 minutes for stress relief annealing;

[0096] Cold rolling: The plate after stress relief annealing is cold rolled for 3 passes, with a cumulative deformation of 50%, and the thickness of the obtained cold rolled plate is about 1.3 mm;

[0097] Annealing treatment: keep the cold-rolled sheet at 800℃ for 30min, and then cool it to room temperature by water quenching.

[0098] Example 5

[0099] This embodiment provides a high-strength and toughness dual-phase low-density steel, the composition of which is as follows: C: 0.61%, Mn: 20.47%, Al: 8.15%, Nb: 0.019%, the rest is Fe and unavoidable impurities, and the mass ratio of Mn to Al is 2.5; the preparation method is as follows:

[0100] Smelting and casting: conventional smelting and continuous casting, the superheat of molten steel is controlled at 15-30℃ during casting, and the thickness of the casting is controlled at 65mm;

[0101] Phosphorus removal: high-pressure water is used to remove phosphorus before the ingot enters the furnace, and the pressure of the dephosphorus removal water is controlled at 375 bar;

[0102] Homogenization: Keep the ingot at 1150℃ for 2 hours for homogenization;

[0103] Phosphorus removal: secondary high-pressure water dephosphorization is carried out before rolling, and the dephosphorization water pressure is controlled at 365 bar;

[0104] Hot rolling: the homogenized ingot is hot rolled for 5 passes, the reduction rate of the 1st to 4th passes is 50%, the reduction rate of the last pass is 35%, the starting rolling temperature is 1100°C, the final rolling temperature is 890°C, and the thickness of the obtained hot rolled plate is 2.6mm;

[0105] Cooling: Cool to the coiling temperature of 640℃ by laminar cooling and coil at this temperature;

[0106] Stress relief annealing: The coiled material is kept at 500℃ for 10 minutes for stress relief annealing;

[0107] Cold rolling: The plate after stress relief annealing is cold rolled for 3 passes, with a cumulative deformation of 50%, and the thickness of the obtained cold rolled plate is about 1.3 mm;

[0108] Annealing treatment: keep the cold-rolled sheet at 950°C for 30 minutes, and then cool it to room temperature by water quenching.

[0109] Comparative Example 1

[0110] This embodiment provides a high-strength and toughness dual-phase low-density steel, the composition of which is as follows: C: 0.61%, Mn: 20.47%, Al: 8.15%, Nb: 0.019%, the rest is Fe and unavoidable impurities, and the mass ratio of Mn to Al is 2.5; the preparation method is as follows:

[0111] Smelting and casting: conventional smelting and continuous casting, the superheat of molten steel is controlled at 15-30℃ during casting, and the thickness of the casting is controlled at 65mm;

[0112] Phosphorus removal: high-pressure water is used to remove phosphorus before the ingot enters the furnace, and the pressure of the dephosphorus removal water is controlled at 375 bar;

[0113] Homogenization: Keep the ingot at 1150℃ for 2 hours for homogenization;

[0114] Phosphorus removal: secondary high-pressure water dephosphorization is carried out before rolling, and the dephosphorization water pressure is controlled at 365 bar;

[0115] Hot rolling: the homogenized ingot is hot rolled for 5 passes, the reduction rate of the 1st to 4th passes is 50%, the reduction rate of the last pass is 35%, the starting rolling temperature is 1100°C, the final rolling temperature is 890°C, and the thickness of the obtained hot rolled plate is 2.6mm;

[0116] Cooling: Cool to the coiling temperature of 640℃ by laminar cooling and coil at this temperature;

[0117] Stress relief annealing: The coiled material is kept at 500℃ for 10 minutes for stress relief annealing;

[0118] Cold rolling: The plate after stress relief annealing is cold rolled for 3 passes, with a cumulative deformation of 50%, and the thickness of the obtained cold rolled plate is about 1.3 mm;

[0119] Annealing treatment: keep the cold-rolled sheet at 650℃ for 30min, and then cool it to room temperature by water quenching.

[0120] Performance Test:

[0121] (1) The dual-phase low-density steels prepared in Examples 1 to 5 and Comparative Example 1 were subjected to XRD testing. Figure 1 As shown by Figure 1 It can be seen that no precipitation of κ carbide was found in the XRD scanning patterns of the dual-phase low-density steels prepared in Examples 1 to 5 and Comparative Example 1.

[0122] (2) The ferrite and austenite contents in the dual-phase low-density steels prepared in Examples 1 to 5 and Comparative Example 1 were quantitatively analyzed using XRD spectrum data using an adiabatic method. The results are shown in Table 1 below:

[0123] Table 1 Ferrite and austenite content in the prepared dual-phase low-density steel

[0124] Serial number Ferrite Austenite Example 1 11.00% 89.00% Example 2 12.60% 87.40% Example 3 13.20% 86.80% Example 4 12.70% 87.30% Example 5 5.60% 94.40% Comparative Example 1 19% 80%

[0125] (2) The dual-phase low-density steels prepared in Examples 1-5 and Comparative Example 1 were subjected to performance tests according to room temperature tensile tests. The results are shown in Table 2 below:

[0126] Table 2 Performance test results of the prepared products

[0127]

[0128]

[0129] As shown in Table 1, the high-strength and toughness low-density steel prepared in Examples 1-5 of the present invention has a yield strength ratio of 0.4 to 0.5 after annealing, a yield strength of 434 to 596 MPa, a tensile strength of 1084 to 1225 MPa, and an elongation of 34 to 39%, and has good work hardening ability and strong plasticity. By comparing Examples 1-3 with Examples 4-5, it can be seen that the addition of Nb significantly improves the strong plasticity of the material.

[0130] In Comparative Example 1, due to the addition of Nb element, the recovery recrystallization of the austenite structure is delayed, and some deformed austenite grains still exist after annealing at 650°C. The deformed structure within the deformed grains will inhibit the work hardening effect of the austenite grains, improve the strength of austenite, increase the strength of the material, and reduce the plasticity. Therefore, the high-strength, toughness, and low-density steel prepared in Comparative Example 1 has a higher yield strength and a higher yield-to-strength ratio, but poor plasticity and a lower strength-plasticity product.

[0131] It is necessary to point out that the above embodiments are limited to further elaboration and explanation of the technical solution of the present invention, and are not further limitations of the technical solution of the present invention. The method of the present invention is only a preferred implementation scheme, and is not used to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high-strength and high-toughness dual-phase low-density steel, characterized in that: The chemical composition of the high-strength and toughness dual-phase low-density steel is as follows: C: 0.58-0.62%, Mn: 18-22%, Al: 7-9%, Nb: 0-0.02%, and the rest is Fe and unavoidable impurities, wherein the mass ratio of Mn to Al is 2.4-2.6; the preparation method is as follows: Smelting and casting: conventional smelting and continuous casting, the thickness of the casting is controlled at 60-150mm; Primary dephosphorization: high-pressure water dephosphorization is performed before the ingot enters the furnace; Homogenization: Keep the ingot at 1100-1200℃ for 1.5-3 hours for homogenization treatment; Secondary dephosphorization: The ingot after homogenization treatment is subjected to secondary high-pressure water dephosphorization; Hot rolling: the ingot after secondary dephosphorization is subjected to multiple hot rolling, wherein the starting rolling temperature is controlled at 1050-1100°C, the final rolling temperature is controlled at 850-910°C, and the ingot is rolled to a thickness of 2.5-4.5 mm; Cooling and coiling: The hot rolled material is cooled to 625-675°C and coiled at this temperature; Stress relief annealing: keep the coiled material at 450-550℃ for 8-15min for stress relief annealing; Cold rolling: After stress relief annealing, multiple cold rolling is carried out, with a cumulative deformation of 45-55%, and the thickness is rolled to 1.15-2.25mm; Annealing treatment: when no Nb is contained, the cold-rolled sheet is kept at 650-950°C for 25-35 minutes, and water quenched to cool to room temperature to obtain the product; when Nb is contained, the cold-rolled sheet is kept at 750-950°C for 25-35 minutes, and water quenched to cool to room temperature to obtain the product.

2. The high-strength and toughness dual-phase low-density steel according to claim 1, characterized in that: During pouring, control the superheat of molten steel at 15-30℃.

3. The high strength and toughness dual-phase low density steel according to claim 1, characterized in that: The pressure of the dephosphorization water is 300-400 bar during the primary dephosphorization, and the pressure of the dephosphorization water is 300-410 bar during the secondary dephosphorization.

4. The high strength and toughness dual-phase low density steel according to claim 1, characterized in that: The ingot after secondary dephosphorization is subjected to 5 hot rolling passes, wherein the reduction rates of the 1st to 4th passes are 40-55%, and the reduction rate of the 5th pass is 25-35%.

5. The high strength and toughness dual-phase low density steel according to claim 1, characterized in that: The hot rolled material is cooled by water curtain cooling or laminar cooling.

6. The high strength and toughness dual-phase low density steel according to claim 1, characterized in that: After stress relief annealing, 2 to 3 cold rolling passes are performed.

7. The high strength and toughness dual-phase low density steel according to claim 1, characterized in that: The mass percentage of Mn is 19.5-20.5%, and the mass percentage of Al is 7.8-8.2%.

8. The high strength and toughness dual-phase low density steel according to claim 1, characterized in that: The homogenization temperature is 1130-1160°C, the final rolling temperature is 875-885°C, and the coiling temperature is 640-660°C.

9. Use of the high-strength and toughness dual-phase low-density steel according to any one of claims 1 to 8 in complex forming of automobile plates.

Citation Information

Patent Citations

  • An annealing process for improving the strength and plasticity of low-density steel and a method for producing low-density steel.

    CN108018494B

  • Low-density steel with yield strength of 700MPa and heat treatment method thereof

    CN115323278A

  • Ageing strengthening high-toughness light steel and manufacturing method thereof

    CN114807772A

  • High-strength and high-plasticity austenite high-manganese steel with bimodal structure and production method

    CN115537677A